Proxemics and Kinesics in Automated Vehicle–Pedestrian Communication: Representing Ethnographic Observations. Issue 10 (October 2019) - Domeyer, Joshua; Dinparastdjadid, Azadeh; Lee, John D.; Douglas, Grace; Alsaid, Areen; Price, Morgan
Since the introduction of automobiles in the early 1900s, communication among elements of the transportation system has been critical for efficiency, safety, and fairness. Communication mechanisms such as signs, lights, and roadway markings were developed to send signals about affordances (i.e., where and when can I go?) and constraints (i.e., where and when can I not go?). In addition, signals among road users such as the hand wave have emerged to communicate similar information. With the introduction of highly automated vehicles, it may be necessary to understand communication signals and apply them to vehicle automation design. However, the question remains: how do we identify the most important interactions that need to be considered for vehicle automation? We propose a method by which we examine the timing of existing vehicle–pedestrian interactions to make conclusions about how the use of time and space can be used as a communication tool. Videos were recorded at representative intersections and crossings in a mid-sized, Midwestern U.S. town. The intersections were chosen based on their potential to elicit interactions with pedestrians and their ubiquity (e.g., four-way stop). Videos were then coded to describe the interactions between vehicles and pedestrians. A focus of this coding was the short stop—stopping before a crosswalk to communicate yielding intent to a pedestrian—which was defined as the time from when the vehicle began to accelerate, after slowing down, to when it reached the crosswalk. Results revealed evidence that vehicle kinematic and spatial cues signal the driver's intent to other road users.